Ventriculo-atrial shunt by percutaneous approach. Technical analysis and case report - Ortiz Vica, A. Emanuel; Saravia Toledo, Alejandro; Morsucci, Edgardo; S. Jaikin, Mario; A. Petre, César (Revista Argentina de Neurocirugía, 2020)
Introduction: Cerebrospinal fluid drainage surgery to the venous system is used as a treatment for hydrocephalus in cases of peritoneal dysfunction. We weigh the percutaneous puncture to insert the distal catheter and use the necessary tools for its correct atrial location. Materials and methods: The study period runs from January 2013 to April 2019. The work includes a total of 45 patients, 24 females and 21 males. The age range is 6 months to 18 years. The modified “Seldinger” technique with ultrasound assistance and intraoperative radioscopic control was used to introduce the catheter distal to the venous system. The minimum follow-up was 1 year at the Hospital de Niños "Ricardo Gutiérrez" in CABA. Results: The causes of hydrocephalus were: myelomeningocele, 17 cases (38 %); congenital, 9 (20 %); tumors, 7 (16 %); post-infective, 6 (14 %); post-hemorrhagic: 5 (11 %); choroid plexus hyperplasia: 1 (2 %). Proximal obstruction occurred in 7 cases (15 %), infections in 5 (11 %), distal dysfunction 4 (8 %) and there were 1 patient (2 %) which exhibited distal venous migration of the intravascular segment. The right internal jugular vein was the site of choice for puncture, 37 cases (82 %); there was almost the same distribution in the location of the frontal and occipital-atrial proximal segments, 23 (51 %) 22 (49 %) respectively; fixed medium pressure valves were most frequently used, total of 40 (89 %). There were no cases of perioperative mortality. Surgical indication involved peritoneal engagement in all cases. Conclusion: Atrial ventricle shunt surgery by percutaneous puncture is a safe technique, not free of complications, which decrease with the correct order of your steps and complement radiology and intraoperative ultrasound.